2019
DOI: 10.1007/s12264-019-00346-z
|View full text |Cite
|
Sign up to set email alerts
|

Thymosin Alpha-1 Inhibits Complete Freund’s Adjuvant-Induced Pain and Production of Microglia-Mediated Pro-inflammatory Cytokines in Spinal Cord

Abstract: Activation of inflammatory responses regulates the transmission of pain pathways through an integrated network in the peripheral and central nervous systems. The immunopotentiator thymosin alpha-1 (Ta1) has recently been reported to have anti-inflammatory and neuroprotective functions in rodents. However, how Ta1 affects inflammatory pain remains unclear. In the present study, intraperitoneal injection of Ta1 attenuated complete Freund's adjuvant (CFA)-induced pain hypersensitivity, and decreased the up-regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 77 publications
3
14
0
Order By: Relevance
“…Mechanical sensitivity. The tactile sensitivity of the hindlimb was assessed in a subset of the animals (yap f/f male mice, yap GFAP -CKO male mice, bFGF-treated and XMU-MP-1-treated WT male mice) using von Frey hair (Faw et al, 2018;Xu et al, 2019). Briefly, the mice were placed under a small, opaque container on an elevated wire mesh to allow access to the plantar surface of the paws.…”
Section: Methodsmentioning
confidence: 99%
“…Mechanical sensitivity. The tactile sensitivity of the hindlimb was assessed in a subset of the animals (yap f/f male mice, yap GFAP -CKO male mice, bFGF-treated and XMU-MP-1-treated WT male mice) using von Frey hair (Faw et al, 2018;Xu et al, 2019). Briefly, the mice were placed under a small, opaque container on an elevated wire mesh to allow access to the plantar surface of the paws.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that spinal cord dysfunction may be one of the underlying pathogenesis of IBS (Zhao et al, 2017 ; Qi et al, 2019 ; Fan et al, 2020 ). As a primary center, the spinal cord plays an important role in the regulation of pain perception (Braz et al, 2014 ; Ji et al, 2019 ; Xu et al, 2019 ). However, the regulation of visceral pain sensitivity at the spinal cord level is rarely reported, so the mechanism remains largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The spinal cord is the first relay area of sensory information from the periphery to the center. It plays a regulatory role in transmitting and integrating pain information 11‐13 . It is, therefore, necessary to explore the role of spinal dorsal horn in enterodynia.…”
Section: Introductionmentioning
confidence: 99%
“…It plays a regulatory role in transmitting and integrating pain information. [11][12][13] It is, therefore, necessary to explore the role of spinal dorsal horn in enterodynia.…”
Section: Introductionmentioning
confidence: 99%